1995
DOI: 10.1590/s0074-02761995000400007
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and hybridization between Culex pipiens and Culex quinquefasciatus (Diptera: Culicidae) in Argentina

Abstract: To better undesrtand the distribution of Culex pipiens and Cx. quinquefasciatus in Argentina, samples were collected from six localities situated in a North-South line from Castelli (Chaco Province) to Puerto Madryn (Chubut Province). Identification was based on the morphology of male genitalia. Only Cx. quinquefasciatus was found in Castelli and Esperanza, while in Rosario, 95.3% belonged to this species and 4.7% represented hybrid forms. Southern samples included only Cx. pipiens. With the purpose of verfyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 0 publications
1
29
0
4
Order By: Relevance
“…This suggested that the border of an area with high levels of hybridization area is approaching the latitude of 33°S, in Brazil. Our findings are in accordance with the observations by Almirón et al (1995) and Humeres et al (1998), which indicated the presence of hybrids in the region of Argentina based on morphology of male genitalia, allele frequencies and experimental crosses. Those authors suggest latitudes between 33-35°S as a possible hybridization region.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This suggested that the border of an area with high levels of hybridization area is approaching the latitude of 33°S, in Brazil. Our findings are in accordance with the observations by Almirón et al (1995) and Humeres et al (1998), which indicated the presence of hybrids in the region of Argentina based on morphology of male genitalia, allele frequencies and experimental crosses. Those authors suggest latitudes between 33-35°S as a possible hybridization region.…”
supporting
confidence: 93%
“…A possible barrier to gene flow between Q and H would be the geographic distribution of Cx. pipiens, which appears to be climatically constrained to south of 33 o S, according to Almirón et al (1995) and Humeres et al (1998).…”
Section: Resultsmentioning
confidence: 99%
“…pipiens forms were differentiated according to the urbanisation type; e.g., in Italy, molestus (urban) and pipiens (rural). Although an overlapping region between the members of the complex was found in Argentina (Almirón et al 1995), the effect of urbanisation on the geographic distribution of the complex remains unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrids of quinquefasciatus/pipiens occur in Uruguay and central Argentina, whilst Cx. pipiens occupies regions southward into Argentina 4,30 .…”
Section: Introductionmentioning
confidence: 99%